2001
DOI: 10.1088/0953-2048/14/2/309
|View full text |Cite
|
Sign up to set email alerts
|

Tensile stress effects on critical current densities of coated conductors

Abstract: Tensile stress dependent critical current densities (Jc) of two types of coated conductors, which were fabricated on a pure Ni tape and a NiCr (13 atomic %) tape respectively, were measured at 77 K. Until the stress reached certain values (Kc), the Jc of each sample was constant, it then began to decrease as the stress was increased further. The Kc for tapes of Ni and NiCr were ~100 MPa and ~270 MPa respectively, which means Kc was enhanced almost three times for the sample fabricated on the NiCr. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The lamination of stabilizers to YBCO coated conductors produced an increase in the stress tolerance. This result suggests that the RABiTS-PLD processed coated conductor has smaller stress tolerance than the IBAD buffered tape on Hastelloy [7]. Figures 6(a) and (b) show the tensile strain dependence of the n-value in YBCO coated conductor.…”
Section: S366mentioning
confidence: 98%
See 1 more Smart Citation
“…The lamination of stabilizers to YBCO coated conductors produced an increase in the stress tolerance. This result suggests that the RABiTS-PLD processed coated conductor has smaller stress tolerance than the IBAD buffered tape on Hastelloy [7]. Figures 6(a) and (b) show the tensile strain dependence of the n-value in YBCO coated conductor.…”
Section: S366mentioning
confidence: 98%
“…Up to now, the I c degradation mechanism and the strain tolerance of Bi-2223 in BSCCO tapes have already been established: I c degradation is caused by the initiation of cracks in the superconducting filaments and the subsequent crack growth [6]. However, the I c degradation mechanism in YBCO coated conductors has not been established yet [7,8]. There are recent reports on the critical current characteristics in YBCO coated conductors under tension and transverse compression at 77 K. Cheggour et al have investigated the effect of strengthening the substrate on the stress or strain tolerance of I c [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…6 It is also known that YBCO/Ni-alloy withstands higher axial stress than YBCO/pure-Ni before ceramic breakage. 7 However, for RABiTS, no information is available on the axial strain at which fractures occur, nor on the relation of this critical strain to the substrate stress-strain curve.…”
mentioning
confidence: 99%
“…Cheggour et al reported that the reversible variation of I c appears below a certain limit [9] and I c decreases rapidly with strain beyond the reversible limit. The strain limit at which I c cannot recover anymore even after the applied strain is relieved is defined as the irreversible strain limit ε irr [9,10]. It is widely accepted that this significant irreversible degradation of I c in CC tapes is attributed to the cracking of the superconducting film due to its innate brittleness.…”
Section: Introductionmentioning
confidence: 99%